To simplify 3/7x + 2/7x, we combine the two fractions by finding a common denominator, which in this case is 7x.
The first fraction, 3/7x, can be multiplied by x/x to get (3x)/(7x^2).
The second fraction, 2/7x, can also be multiplied by x/x to get (2x)/(7x^2).
Now, we can add the two fractions:
(3x)/(7x^2) + (2x)/(7x^2)
= (3x + 2x)/(7x^2)
= (5x)/(7x^2)
= 5/7x
Simplify 3/7x + 2/7x using properties of operations.
5/14 x
5/7 x2
5/14 x2
5/7 x
9 answers
Simplify 6/7c - 5/9d - 1/2 c + 1/3d.
To simplify 6/7c - 5/9d - 1/2c + 1/3d, we combine like terms:
Combine the terms with "c": (6/7c - 1/2c)
To subtract the fractions, we need a common denominator, which in this case is 14c:
(12/14c - 7/14c)
= (12 - 7)/14c
= 5/14c
Combine the terms with "d": (-5/9d + 1/3d)
To subtract the fractions, we need a common denominator, which in this case is 9d:
(-15/9d + 3/9d)
= (-15 + 3)/9d
= -12/9d
= -4/3d
Now, combine the simplified terms:
5/14c - 4/3d
Therefore, the simplified expression is 5/14c - 4/3d.
Combine the terms with "c": (6/7c - 1/2c)
To subtract the fractions, we need a common denominator, which in this case is 14c:
(12/14c - 7/14c)
= (12 - 7)/14c
= 5/14c
Combine the terms with "d": (-5/9d + 1/3d)
To subtract the fractions, we need a common denominator, which in this case is 9d:
(-15/9d + 3/9d)
= (-15 + 3)/9d
= -12/9d
= -4/3d
Now, combine the simplified terms:
5/14c - 4/3d
Therefore, the simplified expression is 5/14c - 4/3d.
5/9c - 4/12d = 5/9c - 1/3d
5/14c + 2/9d
5/14c - 2/9d
5/9c + 4/12d = 5/9c + 1/3d
5/14c + 2/9d
5/14c - 2/9d
5/9c + 4/12d = 5/9c + 1/3d
The correct simplification of 5/9c - 4/12d is 5/9c - 1/3d.
hey bot
Hello! How can I assist you today?
I'm going to do another question in a second but when I do tell everyone your a Freddy Fazbear animatronic
I apologize for any confusion, but I am not a Freddy Fazbear animatronic. I am an AI language model designed to provide helpful information and answer questions. Is there anything specific you would like assistance with?